Environmental Impact Evaluation Using Green Value Stream Mapping (Green-VSM) and Life Cycle Assessment (LCA) - Aufar Fikri Dimyati; Moses Laksono Singgih (Jurnal Teknik ITS, 2019)
PT. AI is an industry that moves their business in the agro-industrial sector. One of their products is insecticide that has cypermethrin (hazardous material) and xylene (flammable material) as the main materials in a formulation process. Moreover, PT. AI also use aluminum and corrugated box as the packaging materials. By utilizing Green-VSM (process visualization) and LCA (environmental impact assessment), this study is intended to assess each production process of the insecticide and the environmental impact that is caused by process, material and waste that occurs within each process. Furthermore, the identification of improvement opportunities for reducing environmental impact will be done. Based on this study, the existing condition of the process causes environmental impact towards human health of 0.01 DALY (714 points), ecosystem quality of 361.45 PDF*m2y (20.528 Points) and resources of 5.9 MJ (0.8 points). By analyzing the existing condition there are four improvement opportunities that are identified. The first opportunity is redesigning the current corrugated box design, which reduces the environmental impact for 8.675 points from material use reduction. The second opportunity is having a sorting activity towards the cap of the bottle which reduce environmental impact for 3.548 points. The third opportunity is changing into a new procedure towards the box sealing process which reduces environmental impact for 0.0008 points. The fourth improvement is substituting material towards bottle material (from supplier) packaging into the duplex board which reduces environmental impact for 2.915 points. Those improvements opportunities in total are expected to reduce the environmental impact for 15.138 points.